Cooperative control of networked multi-robot system - Sithu, Htet. (2010)
The main objective of this report is to document the implementation of the cooperative control algorithm for multi robots. The robots collaborate with the vision localization system to perform target tracking algorithm. The wireless localization system will detect the intruder, then localize intruder and send out the localization information to the pursuer robot through 802.11 wireless network. The pursuer robots calculate a path to intercept the intruder with obstacle avoidance capability. This project involves mostly software development of navigation program for the autonomous robots. As a software development, a LabView platform program has been developed with collision avoidance capability. Although the StarGazer is used for localization in previous projects, the vision based localization system developed by another final year project group is incorporated with the multi robots system to do the localization with relative high accuracy. The pursuer robots uses the built in sonar sensors to ensure the real time obstacle avoidance capabilit